Which duration of unemployment benefits is perceived as being just for which groups? Results from a factorial survey experiment in Germany - Stephan, Gesine; Osiander, Christopher; Senghaas, Monika; Wolff, Richard; Struck, Olaf (Social Policy and Society, 2022)
Welfare states allocate and redistribute resources across different groups. For the social legitimacy of welfare states, public support of redistributive processes and outcomes is crucial. An important aspect in this context is the deservingness or non-deservingness of benefit recipients from the perspective of those who both financially contribute to the system and potentially benefit from it. We invited a random sample of the German labour force to participate in an online-survey. Using a factorial survey experiment, we described fictitious unemployed persons with different attributes and asked survey participants on the just maximum benefit duration for each particular case. Judgements regarding just benefit durations vary along the criteria of reciprocity, control, attitude and need: Respondents grant longer unemployment benefits to older jobseekers, as well as to jobseekers who became involuntarily unemployed, had stable employment careers, have to care for the elderly or are sole earners in the househol